Implementation and Accuracy Testing of a Financial Distress Prediction Model in Indonesian Property and Real Estate Companies - Nia Daliana Dalimunte; Tias Rindu Putri; Nardi Sunardi (Indonesian Development of Economics and Administration Journal, 2023)
This study aims to determine bankruptcy prediction and find the most accurate model for measuring bankruptcy between the Grover, Springate and Zmijewski models for property and real estate companies listed on the Indonesian Stock Exchange (IDX) in 2017 – 2021. The sampling technique used was purposive. sampling on property and real estate companies with a total sample of 31 companies. Data were obtained from the Indonesia Stock Exchange and the company's official website for 2017 – 2021 respectively. Data analysis techniques used the Grover, Springate and Zmijewski models. Data were analyzed using the calculation of the level of accuracy of each model to be able to predict companies experiencing financial distress. The results showed that there were differences between the Grover, Springate and Zmijewski models in predicting financial distress in property and real estate companies listed on the Indonesia Stock Exchange and the most accurate model with the highest accuracy rate of 96.77%, namely the Springate model.